2020
DOI: 10.2169/internalmedicine.4449-20
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Response of Brain Metastasis from <i>EGFR</i>-mutation-positive NSCLC to Dacomitinib

Abstract: The central nervous system efficacy of dacomitinib, a key agent used in the treatment of epidermal growth factor receptor ( EGFR )-mutant non-small-cell lung cancer (NSCLC), is unclear. We herein present our experience in the use of dacomitinib for the treatment of multiple brain metastatic lesions from EGFR-mutation-positive NSCLC in an elderly patient. This case report demonstrates that dacomitinib can be an essential treatment option for patients with brain metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Although the ARCHER 1050 study excluded patients with brain metastasis, subgroup analysis revealed that brain metastases developed as the site of progression in only one patient in the dacomitinib arm as compared with 11 patients in the gefitinib arm, suggesting that dacomitinib may prevent or delay the development of brain metastasis. A case report confirmed the efficacy of dacomitinib for brain metastatic lesions in an elderly patient with an EGFR mutation who had failed on previous lines of TKI treatment and chemotherapy [4]. Due to the limited number of patients in studies reported thus far, this investigation included patients with treatment-naive NSCLC and brain metastases to evaluate the intracranial activity of dacomitinib.…”
Section: Introductionmentioning
confidence: 71%
“…Although the ARCHER 1050 study excluded patients with brain metastasis, subgroup analysis revealed that brain metastases developed as the site of progression in only one patient in the dacomitinib arm as compared with 11 patients in the gefitinib arm, suggesting that dacomitinib may prevent or delay the development of brain metastasis. A case report confirmed the efficacy of dacomitinib for brain metastatic lesions in an elderly patient with an EGFR mutation who had failed on previous lines of TKI treatment and chemotherapy [4]. Due to the limited number of patients in studies reported thus far, this investigation included patients with treatment-naive NSCLC and brain metastases to evaluate the intracranial activity of dacomitinib.…”
Section: Introductionmentioning
confidence: 71%
“…There are only two case reports on dacomitinib therapy for cases previously treated for brain metastases, and they indicated successful treatment with dacomitinib for patients with brain metastases who failed previous EGFR-TKIs. 32,33 Although the treatment induction lines for dacomitinib are different, dacomitinib might be effective against brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al reported that afatinib and osimertinib were effective in four of seven patients with uncommon EGFR mutations found in cerebrospinal fluid ctDNA [ 29 ]. KCSG-LU15-09 study reported that patients with uncommon EGFR mutations taking osimertinib 80 mg orally once per day could achieve an intracranial ORR of 40.0% (2/5) [ 25 ].Several studies have demonstrated the potential efficacy of dacomitinib in EGFR -positive NSCLC with CNS metastases, with ORR ranging from 87.5% to 92.9% and DCR of 100% [ 30 33 ]. A recent study by Li et al showed that intracranial disease control was observed in 92.9% of advanced NSCLC patients with brain metastasis treated with dacomitinib (13/14) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%